THE POSSIBILITIES OF MODERN DIAGNOSTICS OF HERPESVIRUS INFECTIONS IN CHILDREN - A. G. Bokovoy; I. V. Kovalev; L. F. Makkaveeva; O. V. Volodina; N. B. Tanina; Yu. V. Polyakova; N. A. Grishina; V. A. Degtyareva; O. V. Loriya (Детские инфекции (Москва))
Medical history, clinical and laboratory data were studied in 828 children aged from 2 months to 14 years. All of them had different clinical forms of herpesvirus infections (HVI). The combination of the information allows to form the etiologic diagnosis timely and to evaluate the activity of the current infection. Given the polymorphism of clinical symptoms of HVI, it was very important to determine herpesvirus genomes in three media (blood, saliva, urine) by PCR, and high titers of G-antibodies (439 u for CMV and 212.3 u for HHV-6).